Synthesis and Characterization of Novel Hydrazone Based Anti-mutagenic and Antioxidative Agents - Emrah Giziroglua, Cengiz Sarikurkcub, Nurdan Saracc (Journal of Applied Pharmaceutical Science, 2015)
The present study was designed to produce novel hydrazine and evaluate their biological properties including antioxidant, antityrosinase and antimutagenic. 4-allyloxybenzoyl hydrazine (1) reacts with 5-acetyl-1,3-dimethyl barbituric acid (2) and 2-Isonitrosoacetophenone (3) in the presence of acetic acid as a catalyst to produce the hydrazone derivatives 4 and 5 in high yields respectively. The new hydrazone derivatives 4 and 5 have been fully characterized by using multinuclear NMR (1H, 13C) spectroscopy and elemental analysis. The compounds 4 and 5 were studied for their antioxidant and tyrosinase enzyme inhibition activity. In addition the mutagenic and antimutagenic activities were evaluated by Ames Salmonella/ microsome mutagenicity test. The results showed that both of compounds exhibited significant antioxidative and antimutagenic activity and compound 5 has shown moderate tyrosinase inhibition activity. This study suggested that these compounds could be considered as novel bioactive agents in pharmaceutical area.
Keywords: Hydrazone, Oxime, Anti-mutagen, Antioxidant.